ダイ22ジ ナンキョク チイキ カンソク タイ ナツ タイ ホウコク 1980-1981 - 福西, 浩; フクニシ, ヒロシ; Fukunishi, Hiroshi (1983)
P(論文) 第22次南極地域観測隊の夏期行動の概要を述べる。吉田栄夫隊長以下隊員44名と約450tの観測隊物資を搭載した砕氷船「ふじ」は, 1980年11月25日東京港を出航した。「ふじ」は12月31日に昭和基地より約200海里の氷縁に着き, パックアイス帯, 定着氷域を一気に進み1月1日昭和基地より21海里の第1空輸拠点に到達した。その後輸送, 建設作業, 野外調査とも当初計画通りきわめて順調に進行した。本格輸送は1月3日より開始され, 15日までには油以外の物資の輸送はほぼ終了した。そして28日までにすべての物資が輸送された。情報処理棟, 海事衛星地球局, 西オングル島超高層無人観測所, 大型ロンビック短波受信アンテナ等の建設作業も2月3日までにすべて終了した。野外活動では, 昭和基地周辺で生物潜水調査を15回実施した他, プリンスオラフ海岸の天文台岩, あけぼの岩, 新南岩の測地・地質調査, また大陸上での人工地震実験, 気水圏みずほ旅行等を予定通り実施した。2月6日「ふじ」は昭和基地をあとにし, 2月10日から13日の間, 日・ソ超高層共同観測のためマラジョージナヤ基地を訪問した。そして2月19日氷縁を離れ, ポートルイスまでの間, 13ヵ所で海洋物理・化学・生物の停船観測を実施し, 1981年4月20日東京港に帰着した。 The summer operations of the 22nd Japanese Antarctic Research Expedition Party are summarized. The icebreaker FUJI, carrying 450t of cargo and 44 members of the expedition party led by Prof. Y. YOSHIDA, left Tokyo on November 25,1980. The icebreaker arrived at the edge of pack ice, about 200 miles from Syowa Station on December 31,1980. Then, the icebreaker reached the point suitable for air transport, about 27 miles from Syowa Station on January 1,1981. All activities at Syowa Station went on smoothly as previously arranged. The air transport started on January 3,and almost all cargos except fuel were transported to Syowa Station by January 15. The air transport of fuel was accomplished by January 28. The construction works of an information processing building, a MARISAT station, unmanned observatory at West Ongul Island, radio wave receiving antenna and so on were completed by February 3. As field activities, SCUBA diving for biological survey was carried out fifteen times in frozen sea near Syowa Station. Geodetic and geological surveys were carried out at Tenmondai Rock, Akebono Rock, and Sinnan Rocks located on the coastline of Prince Olav Coast. Two field parties for explosion seismic experiment and POLEX-South meteorological experiment made oversnow traverses to Mizuho Station. The icebreaker FUJI left Syowa Station on February 6 in the summer operation. She visited Molodezhnaya Station from February 10 to 13 for the cooperative ...